ADOPSI INOVASI MEDIA KOMUNIKASI-INFORMASI-EDUKASI (KIE) UNTUK MENGUATKAN INDUSTRI KREATIF KOTA PEKALONGAN DI ERA INDUSTRI 4.0 - Maulana, Mohammad Reza; Ismanto, Bambang; Budijanto, Hari Agung; Binabar, Sattriedi Wahyu (BAPPEDA Kota Pekalongan, 2019)
One of the real sectors that currently gets priority from the government is the creative economy, this can be seen by the formation of a special body that is responsible for promoting creative economic growth in Indonesia, through Presidential Regulation of the Republic of Indonesia Number 6 Year 2015 concerning the Creative Economy Agency, the Creative Economy Agency ( Bekraf), but based on the submission of the Governor of Bank Indonesia (BI) Agus Martowardojo at the exhibition of BI assisted MSMEs at Balai Kartini, Jakarta, Friday (8/26/2016), there could be 3, three Indonesians, namely: limited access to credit, creative industries too do not have broad access to international markets, limited human resources and skills. This research aims to realize a communicationinformation-education media that synergizes government institutions, financial institutions, research institutions and creative industries, so as to facilitate the creative industry players to obtain various things needed for development, can help, and improve their positivity, thus increasing the industry creative to be more competitive in the industrial era 4.0. Keywords: Creative industries, Communication-information-education media, Synergizing.